Innovative work behavior: A systematic literature review and conceptual model development - Mohd Faiz Hilmi; Siti Haslina Md Harizan; Yanti Mustapha (Proceedings of AICS - Social Sciences, 2017)
In recent years, marketing innovation evolved into an emerging phenomenon of global interest for marketers, businesses and researchers alike. In light of this development the number of publications focusing on this phenomenon has been rising substantially. The goal of this paper is to provide a structured overview of marketing innovation research by means of a structured literature review. Based on 280 published journal articles, this paper identify, critically analyze and synthesize findings into a conceptual framework of antecedents and consequences of marketing innovation. This paper qualifies as the first attempt to consolidate and analyze relevant research on marketing innovation. Finally, implications for theory, management practice and recommendations for future research are provided.